Progressive failure analysis on two parallel pinned joint glass/epoxy composite plates under the effect of seawater - Orcen, Gurbet; Gur, Mustafa; Turan, Kadir (Sage Publications Ltd, 2014)
This study investigates failure behaviors of woven glass fiber-reinforced epoxy resin composite plates with two parallel pins jointed and under the effect of seawater. The effects of joint geometry and immersion time in seawater were analyzed by experimental and numerical methods. In order to observe the effects of seawater, the samples were kept in seawater for periods of zero, three, and six months. For the observation of the joint geometry effect on the failure behaviour, the edge distance-to-upper hole diameter (E/D), the two hole-to-hole centre diameter (K/D), the distance from the upper or the lower edge of the specimen to the center of the hole-to-hole diameter (M/D), and the width of the specimen-to-hole diameter (W/D) ratios were selected as geometrical parameters. The numerical study where the progressive failure analysis was employed was carried out through a sub-program running in ANSYS 11.0 finite elements program. In order to predict the failure loads and failure types in the numerical analysis, the Tsai-Wu failure criterion was used along with material degradation rules. At the end of the study, it was determined that increase of the immersion time in seawater caused weaker mechanical properties and decrease in failure loads of samples. It was also found that the results of progressive failure analysis were consistent with the experimental results.
Keywords: Progressive failure analysis; seawater effects; pinned joint; composite plates